2015
DOI: 10.1074/jbc.m114.625376
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Scanning Mutagenesis Identifies the Molecular Determinants of Distinct Barttin Functions

Abstract: Background:Barttin is an accessory subunit of renal and inner ear chloride channels. Results: Tryptophan insertion at multiple barttin residues results in non-functional CLC-K/barttin channels with normal intracellular trafficking. Conclusion: Gating of CLC-K/barttin channels is more sensitive to tryptophan insertion in barttin than intracellular trafficking. Significance: Understanding the molecular basis of CLC-K modification by its accessory subunit barttin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Cells co-expressing W610X hClC-Kb with barttin exhibited slightly larger mean current amplitudes than cells expressing the channel alone (at Ϫ105 mV: Ϫ0.71 Ϯ 0.10 nA, n ϭ 8; p ϭ 0.02 versus hClC-Kb W610X alone). Previous biochemical and microscopic data have demonstrated that hClC-Kb inserts into the plasma membrane even in the absence of barttin (6,26,28). The absence of measurable currents from cells expressing WT hClC-Kb alone indicates that hClC-Kb remains inactive without barttin (6).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Cells co-expressing W610X hClC-Kb with barttin exhibited slightly larger mean current amplitudes than cells expressing the channel alone (at Ϫ105 mV: Ϫ0.71 Ϯ 0.10 nA, n ϭ 8; p ϭ 0.02 versus hClC-Kb W610X alone). Previous biochemical and microscopic data have demonstrated that hClC-Kb inserts into the plasma membrane even in the absence of barttin (6,26,28). The absence of measurable currents from cells expressing WT hClC-Kb alone indicates that hClC-Kb remains inactive without barttin (6).…”
Section: Resultsmentioning
confidence: 95%
“…Although such effect on the common gate of human CLC-K channel function cannot be directly demonstrated, we recently demonstrated that hClC-Ka/barttin channels exhibit an open common gate (27). Moreover, scanning mutagenesis demonstrated similar effects of tryptophan insertion at each transmembrane domain of barttin on common gating of rClC-K1 and function of hClC-Ka (28). Taken together, these findings strongly suggest that barttin activates human and rodent CLC-K by the same mechanisms, i.e.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations